Controlling the Growth Kinetics and Optoelectronic Properties of 2D/3D Lead–Tin Perovskite Heterojunctions. Issue 51 (11th November 2019) - Ruggeri, Edoardo; Anaya, Miguel; Gałkowski, Krzysztof; Delport, Géraud; Kosasih, Felix Utama; Abfalterer, Anna; Mackowski, Sebastian; Ducati, Caterina; Stranks, Samuel D.
Abstract: Halide perovskites are emerging as valid alternatives to conventional photovoltaic active materials owing to their low cost and high device performances. This material family also shows exceptional tunability of properties by varying chemical components, crystal structure, and dimensionality, providing a unique set of building blocks for new structures. Here, highly stable self‐assembled lead–tin perovskite heterostructures formed between low‐bandgap 3D and higher‐bandgap 2D components are demonstrated. A combination of surface‐sensitive X‐ray diffraction, spatially resolved photoluminescence, and electron microscopy measurements is used to reveal that microstructural heterojunctions form between high‐bandgap 2D surface crystallites and lower‐bandgap 3D domains. Furthermore, in situ X‐ray diffraction measurements are used during film formation to show that an ammonium thiocyanate additive delays formation of the 3D component and thus provides a tunable lever to substantially increase the fraction of 2D surface crystallites. These novel heterostructures will find use in bottom cells for stable tandem photovoltaics with a surface 2D layer passivating the 3D material, or in energy‐transfer devices requiring controlled energy flow from localized surface crystallites to the bulk. Abstract : Lead–tin‐based perovskites represent a promising route for achieving low‐gap perovskite solar absorbers and light‐emitters. Films composed of heterostructures of 2D and 3D lead–tin perovskite domains are fabricated with distinctively unique optoelectronic properties. These tunable structures enhance the understanding of the growth and optoelectronic properties of 2D/3D perovskite heterojunctions, and will see use in energy funneling and passivating structures.